The Sli.do as a tool for classroom participation and interaction - Monteiro, Jean Carlos da Silva; Rodrigues, Sannya Fernanda Nunes (Educação, Escola & Sociedade, 2020)
This paper is a study about Sli.do and aims at describing its potential in engaging and promoting interactivity in the classroom environment. The study discusses how learning apps can be used by teachers to engage and promote student’s interactivity, especially for those who are shyer. The text discusses the influence that shyness has on education. Moreover, the study presents the concept of app-learning in order to contribute to further understanding of Sli.do as a suitable tool capable of solving the problem of shyness in the academic environment. Results evidenced that Sli.do encourages students’ participation and support the learning-by-doing process, once it stimulates the development of students’ skills by facilitating their engagement and understanding about the knowledge acquired during the classes.